PENGARUH LOCUS OF CONTROL EKSTERNAL, KOMITMEN ORGANISASI, KESADARAN ETIS TERHADAP INTENSI MELAKUKAN WHISTLEBLOWING (Studi Empiris pada Bank Perkreditan Rakyat di Provinsi Riau) - Ade Kurniati; Rita Anugerah; Novita Indrawati (PEKBIS, 2019)
This study aims to determine the cause of whistleblowing intention. By using thetheory of planned behavior, this study specifically investigated the impact of locus ofcontrol, organizational commitment, and ethical awareness toward intention towhistleblowing. The study used survey questionnaires from 79 employees at 35Rural Banks (Local Banks) in Riau Province. Furthermore, Partial Least Square(PLS) analysis is used to test the research hypothesis. The results revealed thatlocus of control, organizational commitment, and ethical effectiveness had a positiveeffect on the intention to whistleblowing.